Manipulating the contribution of approach-avoidance to the perturbation of economic choice by valence - Wright, Nicholas D.; Morris, Laurel S.; Guitart Masip, Marc; Dolan, Raymond J. (Frontiers in Neuroscience, 2013)
Economic choices are strongly influenced by whether potential outcomes entail gains or losses. We examined this influence of outcome valence in an economic risk task. We employed three experiments based on our task, each of which provided novel findings, and which together better characterise and explain how outcome valence influences risky choice. First, we found that valence perturbed an individual’s choices around that individual’s base-level of risk-taking, a base-level consistent across time and context. Second, this perturbation by valence was highly context dependent, emerging when valence was introduced as a dimension within a decision-making setting, and being reversed by a change in task format (causing more gambling for gains than losses and the reverse). Third, we show this perturbation by valence is explicable by low-level approach-avoidance processes, an hypothesis not previously tested by a causal manipulation. We revealed such an effect, where individuals were less disposed to choose a riskier option with losses when they had to approach (go) as opposed to avoid (nogo) that option. Our data show valence perturbs an individual’s choices independently of the impact of risk, and causally implicate approach-avoidance processes as important in shaping economic choice.